ANALISIS MANAJEMEN STRATEGI BADAN AMIL ZAKAT (BAZ) TERHADAP PENYALURAN DANA DALAM MENGURANGI KEMISKINAN DI DESA JIRAK KECAMATAN SAJAD - Zola Mei Hendri Zola Mei Hendri (Sebi : Studi Ekonomi dan Bisnis Islam, 2022)
Analysis of Strategic Management of the Amil Zakat Agency (BAZ) for Distribution of Funds in Reducing Poverty in Jirak Village, Sajad District. Final Project, 2021 Zakat is property that must be issued by a Muslim or business entity to be given to those who are entitled to receive it in accordance with Islamic law. Therefore, zakat can function as a source of socio-economic funds for Muslims. The Amil Zakat Agency (BAZ) Jirak Village, Sambas Regency was formed to achieve efficiency, efficiency and accountability in the management of zakat, infaq and alms funds (ZIS) so that it can increase the participation of Sambas Regency Muslims in the framework of complete human development by collecting and managing funds zakat, infaq and alms (ZIS). The BAZ Sambas strategy in channeling zakat funds is through a productive mustahik empowerment program. The form of the program in general is strengthening business programs for economically weak communities by providing business capital assistance in the form of benevolent financing (qardhul hasan). This study aims to determine the strategy of BAZNAS in Jirak Village, Sajad District in distributing zakat funds to reduce poverty and the views of Islamic Law on the model of distributing zakat funds in Jirak Village. This study used a qualitative research method by posing several questions to the BAZNAS of Jirak Village and the people of Jirak Village. The results of this study are to explain the strategy of the Sambas Regency BAZNAS in channeling zakat funds to reduce poverty and the view of Islamic law on the model of channeling zakat funds at BAZNAS Jirak Village. The strategy undertaken by BAZNAS Jirak Village is (1) Planning, namely BAZNAS Jirak Village manages the house renovation and business capital programs that have been set by the Sambas District Government. (2) The management of the collection and distribution of zakat funds in Jirak Village, namely BAZNAS Jirak Village conducts socialization so that the community can distribute their zakat funds through BAZNAS Jirak Village while for the distribution of zakat funds, BAZNAS Jirak Village provides it to the less fortunate and those who have the skills to the community can be empowered.